Evaluation of the covariation between leukotriene B4, prostaglandin E2, and hematologic inflammatory parameters in a canine pentylenetetrazole-induced seizure model - Koo, Yoonhoi; Yun, Taesik; Chae, Yeon; Lee, Dohee; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Neuroscience, 2024)
BackgroundSeizures can cause as well as result from neuroinflammation. This study was performed to identify the hematologic inflammatory parameters (HIPs) and inflammatory mediators that change after a single seizure in a canine pentylenetetrazole (PTZ)-induced seizure model.MethodsFive healthy Beagle dogs were used in this study. A 3% solution of PTZ was infused until the occurrence of generalized convulsion. Two separate experiments were conducted to observe changes in HIPs over short and long time periods. Blood sampling time points were divided into two periods as follows: short period (baseline, 30, 60, 90, and 120 min after seizure induction) and long period (baseline, 2, 6, 12, 24, and 48 h after seizure induction). The HIPs were calculated, and the serum prostaglandin E2 (PGE2) and leukotriene B4 (LTB4) concentrations were estimated using enzyme-linked immunosorbent assay.ResultsSignificant changes (p < 0.05) in various HIPs were observed at different time point as follows: neutrophil × monocyte (90 min), neutrophil-to-lymphocyte ratio (60, 90, and 120 min), lymphocyte to monocyte ratio (60 min, 90 min, 120 min, 2 h, 12 h, and 24 h), platelet-to-albumin ratio (90 min), lymphocyte percentage × serum albumin concentration (LA; 60 min, 90 min, 120 min, 2 h), and neutrophil × platelet (6 h). LTB4 concentrations were significantly increased (p < 0.05) at 60 and 90 min, and 2, 6, and 48 h after seizure induction. PGE2 was significantly increased only 6 h after seizure induction (p < 0.05). LA was one of the HIPs that demonstrated a correlation with LTB4 concentration and showed significant changes that could be observed for a long-period (p < 0.05, r = −0.4194).ConclusionThe LA was the only HIP that reflected seizure-associated neuroinflammation. The 5-lipoxygenase pathway might be related to seizure-associated neuroinflammation.